Expanding the spectrum of SMAD3‐related phenotypes to agnathia‐otocephaly. Issue 4 (26th February 2020) - Meier, Nicole; Bruder, Elisabeth; Miny, Peter; Tercanli, Sevgi; Filges, Isabel
Abstract: Background: Agnathia‐otocephaly is a rare and lethal anomaly affecting craniofacial structures derived from the first pharyngeal arch. It is characterized by agnathia, microstomia, aglossia, and abnormally positioned auricles with or without associated anomalies. Variants affecting function of OTX2 and PRRX1, which together regulate the neural crest cells and the patterning of the first pharyngeal arch as well as skeletal and limb development, were identified to be causal for the anomaly in a few patients. Methods: Family‐based exome sequencing (ES) on a fetus with severe agnathia‐otocephaly, cheilognathopalatoschisis, laryngeal hypoplasia, fused lung lobes and other organ abnormalities and mRNA expression analysis were performed. Results: Exome sequencing detected a de novo SMAD3 missense variant in exon 6 (c.860G>A) associated with decreased mRNA expression. Variants in SMAD3 cause Loeys–Dietz syndrome 3 presenting with craniofacial anomalies such as mandibular hypoplasia, micro‐ or retro‐gnathia, bifid uvula and cleft palate as well as skeletal anomalies and arterial tortuosity. The SMAD3 protein acts as a transcriptional regulator in the transforming growth factor β (TGFB) and bone morphogenetic (BMP) signaling pathways, which play a key role in the development of craniofacial structures originating from the pharyngeal arches. Conclusion: Agnathia‐otocephaly with or without associated anomalies may represent the severe end of a phenotypic spectrum related to variants in genes in the interacting SMAD/TGFB/BMP/SHH/FGF developmental pathways. Abstract : Variants affecting function of OTX2 and PRRX1, which together regulate neural crest cells and the patterning of the first pharyngeal arch as well as skeletal and limb development, were identified to be causal for aganthia‐otocephaly in a few patients. Using family‐based exome sequencing we found a pathogenic variant in SMAD3 . We expand the clinical spectrum of SMAD3 variants from Loeys‐Dietz syndrome 3 and suggest that agnathia‐otocephaly with or without associated anomalies may represent the severe end of a phenotypic spectrum related to variants in genes in the interacting SMAD/TGFB/BMP/SHH/FGF developmental pathways.